2018
DOI: 10.1039/c8en00189h
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-induced structural changes in lung surfactant membranes: an X-ray scattering study

Abstract: Low concentrations of cationic silica nanoparticles impact lung surfactant membrane structure while anionic nanoparticles have minimal effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…This interaction, which occurs with an LS having an average negative charge, is enhanced as the charge density of the particles is increased [208]. The different impact of charged particles on the interfacial properties of lipid mixtures and LS formulations containing proteins was independently demonstrated by Behyan et al [189] in their study about the interaction of positively and negatively charged silicon dioxide particles with different LS models, a DPPC/POPG mixture, and an extract from calf lung (Infasurf). They found that whereas the behavior of Infasurf was only modified by the cationic particles, that of the natural extract was influenced by both, positively and negatively charged particles.…”
Section: Role Of Particle Surface Charge and Wettability On Their Int...mentioning
confidence: 94%
See 2 more Smart Citations
“…This interaction, which occurs with an LS having an average negative charge, is enhanced as the charge density of the particles is increased [208]. The different impact of charged particles on the interfacial properties of lipid mixtures and LS formulations containing proteins was independently demonstrated by Behyan et al [189] in their study about the interaction of positively and negatively charged silicon dioxide particles with different LS models, a DPPC/POPG mixture, and an extract from calf lung (Infasurf). They found that whereas the behavior of Infasurf was only modified by the cationic particles, that of the natural extract was influenced by both, positively and negatively charged particles.…”
Section: Role Of Particle Surface Charge and Wettability On Their Int...mentioning
confidence: 94%
“…However, the use of DPPC as a model for understanding the performance of LS is rather limited because its inefficiency in the reservoir formation and its slow respreading at the interface during expansion. This has driven the research on the use of more complex models, including DPPC in combination with other lipids or fatty acids, e.g., palmitic acid, cholesterol or DOPC (1,2-dioleoylsn-glycero-3-phosphocholine), among others [117,136,165,173,[188][189][190][191], which provide a simplified picture of the complex behavior of LS under physiological conditions. The use of these models can provide a deeper understanding of the behavior of LS films because some studies have evidenced the important role of specific lipids, e.g., 1-palmitoyl-2-oleoylsn-glycero-3-phosphocholine (POPC) or 1-palmitoyl-2-oleoyl-sn-glycero-3-(phospho-rac-(1glycerol)) (POPG), on the modulation of the phase behavior of LS film [173,189,190,192].…”
Section: Chemistry Of Lung Surfactant Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values concord with the tilt angles of 12-30° reported for Langmuir monolayers and solid-supported bilayers of dialkylphosphatidylcholines in the condensed or gel phase. [67][68][69][70][71] Overall, the <P2> values and tilt angles mean that the difference in the transition temperatures of the two leaflets observed by AFM is not due to an initial difference in the conformational order or orientation of the acyl chains.…”
Section: Asymmetric Dppc Bilayersmentioning
confidence: 99%
“… 11 , 12 However, the current understanding of the potential biophysical changes associated with particle inhalation is far from clear. On one hand, the interaction of particles with LS alters their surface tension, phase behavior, and interfacial structure, 13 , 14 whereas on the other hand particles are widespread in therapy and diagnostic. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%